SYNTHESIS, CHARACTERIZATION OF A NEW SCHIFF BASE POLYMERS AND EVALUATION OF THEIR ANTICANCER ACTIVITY - Mankhi, Zainab; Hussain, Mahmoud; Ali, Hanan (International Journal Multidisciplinary (IJMI), 2025)
Objective: A novel bis-Schiff base was synthesized through the condensation of benzidine with 4-hydroxybenzaldehyde. Method: This precursor was subsequently subjected to polycondensation with phthalic and terephthalic acids, facilitated by ZnCl₂, yielding two distinct polymers designated P1 and P2. The structural integrity of P1 (derived from phthalic acid) and P2 (derived from terephthalic acid) was rigorously confirmed using FTIR spectroscopy. The spectra distinctly showed a strong imine (C=N) stretching vibration (approximately 1645 cm⁻¹) and the notable appearance of new ester or amide carbonyl bands (around 1710–1720 cm⁻¹) subsequent to polymerization. Thermogravimetric analysis (TGA) indicated that both polymers undergo decomposition primarily in two stages; however, P2 demonstrated significantly enhanced thermal stability, with a decomposition onset near 300 °C, compared to P1. The potential anticancer activity of P1 and P2 was evaluated against human breast cancer (MCF-7) cells employing MTT viability assays. Result: Both polymers exhibited dose-dependent cytotoxicity. Notably, polymer P2 proved to be more potent, displaying an IC₅₀ value of approximately 138 μg/mL, whereas P1 showed an IC₅₀ of about 173 μg/mL. It is noteworthy that these IC₅₀ values fall within the range previously reported (120–200 μg/mL) for comparable Schiff-base polymers by researchers at the University of Basrah. Novelty: The observed higher efficacy of P2 is reasonably attributed to its more planar structure derived from the terephthalate units, which might facilitate enhanced cellular uptake or interaction. These findings compellingly demonstrate that subtle modifications in polymer architecture (specifically, angular versus linear diacid linkers) can substantially influence both thermal robustness and anticancer efficacy, thereby underscoring the considerable promise of Schiff-base polymers as versatile multifunctional biomaterials.